Image 1_Immune-related RELT drives clear cell renal cell carcinoma progression through JAK/STAT signaling pathway activation.tiff - Yini Wang (410389) (2025)
Objective The experiment aims to verify the function of Tumor Necrosis Factor Receptor Superfamily Member 19L (RELT) in clear cell renal cell carcinoma (ccRCC). Methods The relationship between differential expression of RELT in ccRCC and clinical prognosis was investigated based on data from the Gene Expression Omnibus database (GEO) and The Cancer Genome Atlas (TCGA) databases. Ex vivo and in vivo experiments were applied to validate the function of RELT in ccRCC. The pathways through which RELT exerts its function were explored using analyses such as Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes Enrichment Analysis (KEGG), and Gene Set Enrichment Analysis (GSEA). In addition, we applied the algorithms xCELL, Estimating the Proportion of Immune and Cancer cells (EPIC), CIBERSORT, Tumor Immune Estimation Resource (TIMER), and Tumor Immune Dysfunction and Exclusion (TIDE) to analyze the effect of RELT on the ccRCC tumor immune microenvironment. Results RELT is highly expressed in ccRCC tissues and portends poor prognosis. Functional assays indicate that RELT promotes malignant biological behavior in ccRCC cells. Subsequently, enrichment analysis revealed that RELT functions mainly through humoral immunity, cellular chemotaxis, and cytokine regulation and may serve as a molecule for predicting prognosis in ccRCC. Immune infiltration analysis showed that RELT was significantly associated with immune cells such as B Cells, CD8+ T Cells, CD4+ T Cells, and Macrophages and may affect the tumor immune microenvironment of ccRCC by influencing macrophages. Conclusion RELT promotes the development of ccRCC and may play a role in regulating the tumor immune microenvironment, which affects the prognosis of ccRCC patients, and RELT may become a new biomarker associated with immune infiltration in ccRCC.